THE EFFECT OF OCCUPATIONAL HEALTH AND SAFETY (OHS) MANAGEMENT ON SAFETY BEHAVIOR OF WORKERS AT CONSTRUCTION SERVICE COMPANY IN SURABAYA - Badriyah, Lailatul; Noeroel Widajati; Dani Nasirul Haqi; Meirina Ernawati (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Compared to manufacturing industry, construction has a unique characteristic. These characteristics cause construction projects to have dangerous conditions and make them vulnerable to an occupational accident. Purpose: To analyze the influence of Occupational Health and Safety (OHS) management on the building construction workers' safety behavior at construction service company Surabaya. Method: This research classification is observational and a cross-sectional research with analytic nature. This research is conducted over 4 months. The research sample amounted to 53 workers. Its dependent variable is safety behavior (OHS behavior) with the top manager's commitment, OHS procedure regulation, communication, worker's competency, interpersonal relationship and physical hazard as its independent variables. Data is descriptively analyzed in the form of a frequency table and cross-tabulation. A statistical test is performed by using the chi-square test with α=0.05. Result: Management commitment (p-value=0.001) and OHS procedure regulation (p-value=0.029) significantly affect the safety behavior implementation to the worker. Conclusion: Two Independent variables which affect the safety behavior of the building construction worker at construction service company Surabaya ware management commitment (X1) and OHS procedure regulation (X2). The regulation of OSH procedures must be communicated, promoted to workers, and supervision of workers can be increased as a form of good commitment and given support by providing rewards for workers who have implemented safe behavior properly and providing punishment for workers who conduct unsafe behavior.